2020
DOI: 10.1111/maps.13459
|View full text |Cite
|
Sign up to set email alerts
|

The role of Bells in the continuous accretion between the CM and CR chondrite reservoirs

Abstract: CM meteorites are dominant members of carbonaceous chondrites (CCs), which evidently accreted in a region separated from the terrestrial planets. These chondrites are key in determining the accretion regions of solar system materials, since in Mg and Cr isotope space, they intersect between what are identified as inner and outer solar system reservoirs. In this model, the outer reservoir is represented by metal-rich carbonaceous chondrites (MRCCs), including CR chondrites. An important question remains whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 77 publications
(145 reference statements)
2
25
0
Order By: Relevance
“…The Cr isotope data for doping and external precision tests are reported in Table 2 and combined with literature data from Schiller et al (2014). In Table 3, we compare the 55 Mn/ 52 Cr and Cr isotope data for the same chondrites measured in this and previous studies (Go ¨pel et al, 2015;Jenniskens et al, 2012;Kadlag et al, 2019;Langbroek et al, 2019;Mougel et al, 2018;Moynier et al, 2007;Petitat et al, 2011;Qin et al, 2010;Sanborn et al, 2019;Schiller et al, 2014;Trinquier et al, 2007;2008b;van Kooten et al, 2020van Kooten et al, , 2016Williams et al, 2020;Zhu et al, 2020aZhu et al, , 2020b. The averaged group Cr isotope data and 55 Mn/ 52 Cr ratios of all the chondrites are reported in Table 4.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The Cr isotope data for doping and external precision tests are reported in Table 2 and combined with literature data from Schiller et al (2014). In Table 3, we compare the 55 Mn/ 52 Cr and Cr isotope data for the same chondrites measured in this and previous studies (Go ¨pel et al, 2015;Jenniskens et al, 2012;Kadlag et al, 2019;Langbroek et al, 2019;Mougel et al, 2018;Moynier et al, 2007;Petitat et al, 2011;Qin et al, 2010;Sanborn et al, 2019;Schiller et al, 2014;Trinquier et al, 2007;2008b;van Kooten et al, 2020van Kooten et al, , 2016Williams et al, 2020;Zhu et al, 2020aZhu et al, , 2020b. The averaged group Cr isotope data and 55 Mn/ 52 Cr ratios of all the chondrites are reported in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…In Table 4, combining these new measurements with literature data (Go ¨pel et al, 2015;Qin et al, 2010;Trinquier et al, 2007;van Kooten et al, 2020;Zhu et al, 2021) results in an updated e 54 Cr sequence: CI ! CH !…”
Section: Updated E 54 Cr Sequence and Intra-group E 54 Cr Heterogeneity Of Carbonaceous Chondritesmentioning
confidence: 96%
See 2 more Smart Citations
“…A recent study utilizing Mg and Cr isotopes from CM chondrites and chondrules concluded that many anomalous aspects of Bells could be explained by the prolonged accretion of outer protoplanetary disk material onto CM chondrite parent bodies (Van Kooten et al. 2020). However, the more sunward location (i.e., lower orbital distances) of the CMs would have precluded the accretion of larger amounts of the more volatile species such as NH 3 (needed for formation of amino acids and amines).…”
Section: Discussionmentioning
confidence: 99%